Pemberdayaan Ibu-Ibu Rumah Tangga Desa Barbaran Melalui Pelatihan Pembuatan Kue Panyaram Tradisional untuk Meningkatkan Kesejahteraan Ekonomi - Jureid Jureid; Mukhlis Mukhlis (Jurnal Nusantara Berbakti, 2025)
The community empowerment program through traditional panyaram cake-making training in Barbaran Village, Panyabungan Barat District, Mandailing Natal Regency, aims to enhance the entrepreneurial skills of housewives and strengthen community-based economics. Despite its potential, Barbaran Village faces challenges due to limited skills and access to training. The program is carried out in three stages: preparation, implementation, and mentoring. The preparation stage involves identifying targets, forming groups, and planning activities. The implementation phase includes practical training in making panyaram cakes, guided by experienced instructors. Finally, the mentoring stage provides participants with business tools and support in managing business administration. This program significantly improved participants' skills in producing high-quality panyaram cakes, attractive packaging, and understanding entrepreneurship, including business legality. It also boosted participants’ self-confidence and social solidarity, paving the way for new business opportunities and enhancing family welfare. By optimizing local resources, the program enables the women of Barbaran Village to establish panyaram cakes as a flagship product and compete in the local market. The program’s sustainability is expected to create local job opportunities, foster independent economic growth, and support the community's long-term development. This initiative highlights the potential of traditional culinary products to drive community empowerment and economic resilience.